TUMOR OTAK PRIMER PADA ANAK DI RSUP DR. M. DJAMIL PADANG PADA TAHUN 2019-2021 - Siti Nawal Sumaiyah; Rahmi L; Roni ES (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Background: Primary brain tumor is one of the disease that often occur in childhood and occupy second place after leukemia. However, the data on this matters are not widely study in Indonesia or in the world. Brain tumor have two peaks, at the age of children and at adult age. There are several primary brain tumor with various symptoms as well. Primary brain tumor can be located at infratentorial or supratentorial of the brain. The therapy that can be perform are tumor removal, radiotherapy or chemotherapy and complication that can be seen on this case are hydrocephalus and brain herniationObjective: This study aim to determine primary brain tumor at RSUP. Dr. M. Djamil Padang in 2019-2021. Methods: This study is retrospective descriptive study and was conducted by evaluating the medical record of pediatric primary brain tumor at RSUP. Dr. M. Djamil Padang in 2019-2021 with a total sample of 27 patients. Results The result of this study is that most pediatric primary brain tumor accur in boys (51,58%) at the age of 10 – 14 years old. The most commom tumor are medulloblastoma (44,83%) with commom symptom are headache (51,72%). Infratentorial was the comman place for the tumor to occur in this study. The treatment are tumor removal (48,28%) and the complication was hydrocephalus (58,62%). Conclusion: The conclusion of this research was at RSUP. Dr. M. Djamil Padang many pediatric primary brain tumor occur in boys rather than girls and the common age for this disease are 10 – 14 years old with common tumor are medulloblastoma. Symptoms that are oftem occur are headache and the locations are at the infratentorial with the common therapy are tumor removal. Most sample obtained hydrocephalus in this study